2018
DOI: 10.1108/mabr-07-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Measurement challenges of supply chain performance in complex shipping environments

Abstract: Purpose Logistics service performance measurement (PM) is a fundamental activity pertaining to the achievement of logistics goals and the improvement of services. The choice of logistics PM criteria depends on stakeholder goals and expectations, including logistics service providers, customers and government and regulatory institutions. PM is especially challenging in areas where high values are at stake, several actors are involved and uncertainty about cause-and-effect relations is high. This paper aims to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Mariano et al [42] integrated logistics performance index (LPI) and carbon dioxide emission index, constructed a low-carbon logistics performance index, and ranked 104 countries to determine the countries with the best performance in low-carbon logistics. Panayides et al [43] investigated the performance measurement of offshore oil and gas logistics and put forward a series of key performance indicators of offshore logistics aiming at specific environment, with special emphasis on the particularity of harsh operating environment. In addition, Tse et al [44] also pointed out that artificial intelligence technology has gained great attention in improving the flexibility of supply chain management and logistics operation and can enable the logistics industry to achieve high-level service performance.…”
Section: Relationship Between Logistics Performance and Environmental Degradationmentioning
confidence: 99%
“…Mariano et al [42] integrated logistics performance index (LPI) and carbon dioxide emission index, constructed a low-carbon logistics performance index, and ranked 104 countries to determine the countries with the best performance in low-carbon logistics. Panayides et al [43] investigated the performance measurement of offshore oil and gas logistics and put forward a series of key performance indicators of offshore logistics aiming at specific environment, with special emphasis on the particularity of harsh operating environment. In addition, Tse et al [44] also pointed out that artificial intelligence technology has gained great attention in improving the flexibility of supply chain management and logistics operation and can enable the logistics industry to achieve high-level service performance.…”
Section: Relationship Between Logistics Performance and Environmental Degradationmentioning
confidence: 99%
“…The literature discusses general shipbuilding industry performance is sparse. Panayides et al (2018) presented key performance indicators (KPIs) for offshore logistics with a special emphasis on a harsh operational environment. Sanderson and Cox (2008) found that the design and build process used in the shipbuilding industry introduces radical unpredictability into the demand for functional components of naval vessels.…”
Section: Introductionmentioning
confidence: 99%
“…This interest could be observed with the recent developments in the topic of ranking cities and locations within the maritime cluster context (Verhetsel and Sel, 2009; Jacobs et al , 2011; Zhang and Lam, 2013a, b). The rankings use diverse set of indicators, with benchmarking reports produced by research organisations, economic consulting organisations, maritime industry organisation and major global consulting organisations (Mudambi, 2008; Narula, 2002; Panayides et al , 2018). These international studies and publications of ranking maritime locations have garnered widespread international business (IB) media coverage, reflecting the interest of business communities on this subject, as multi-national enterprises (MNEs) continue to search and source for locations that will contribute to their own competence creation through their subsidiaries (Meyer et al , 2011, Mudambi and Swift, 2012; Narula, 2002) and hence build competitive advantage by integrating the knowledge attained at its subsidiaries with its international operations (Andersson et al , 2014).…”
Section: Introductionmentioning
confidence: 99%